2012
DOI: 10.1007/s10935-012-0269-9
|View full text |Cite
|
Sign up to set email alerts
|

Association Between School Engagement and Disclosure of Suicidal Ideation to Adults Among Latino Adolescents

Abstract: We examined associations between Latino adolescents’ school engagement and their likelihood of disclosing suicidal ideation (SI) to adults and asking help for SI. Analyses were conducted on the entire sample of 14 schools and a second set of analyses was conducted with Latino youth from “Latino-representative” high schools. The criterion for ‘Latino-representative’ was that ≥10% of the school’s total population consisted of Latinos. Among 663 Latino/a adolescents from all 14 high schools, 110 reported SI in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 64 publications
1
23
1
Order By: Relevance
“…Our results suggest a dose-response effect between suicide and connection with teachers and other school adults. Previous research suggests that the association between suicide attempt and school engagement differs by sex, 3,4,45 but our study showed only slight variations in the effect of positive adult relationships on female and male students. In the multivariate model in our study, a school adult believing they would be successful was protective only for girls and a school adult listening was protective only for boys.…”
Section: Connection With Teachers and Other School Adultscontrasting
confidence: 88%
“…Our results suggest a dose-response effect between suicide and connection with teachers and other school adults. Previous research suggests that the association between suicide attempt and school engagement differs by sex, 3,4,45 but our study showed only slight variations in the effect of positive adult relationships on female and male students. In the multivariate model in our study, a school adult believing they would be successful was protective only for girls and a school adult listening was protective only for boys.…”
Section: Connection With Teachers and Other School Adultscontrasting
confidence: 88%
“…Students responding affirmatively to SI were asked to answer the following question: “Who was the first person you told about these (suicidal) thoughts?” Response choices were: mother, father, sibling, other relative, spouse/partner, boyfriend/girlfriend, friend, roommate, co‐worker, resident advisor, professor, college/off campus mental health provider, psychiatrist, counselor, clergy, or other with options of either “yes/no.” Due to the low response rate (mean = 10%) of individual responses, likely a result of number of options a student could choose from, we combined all individuals a student reported in a dichotomous measure of 1 = help or 0 = no help reported (De Luca & Wyman, ).…”
Section: Methodsmentioning
confidence: 99%
“…Although this study used data from a 20‐year‐old study which did not have a nationally representative sample, Morrison and Downey () found NHW college students disclosed at higher rates than REM students. Their findings are not surprising, as racial/ethnic minorities traditionally utilize mental health services less than NHWs (Early & Akers, ), including Latinos with recent SI (De Luca & Wyman, ) and among college samples (Walker et al., ). Lower rates in minority mental health care utilization could be linked to parental attitudes of behavioral care (Zimmerman, ) even though the need for services may be equal or greater than that for other racial/ethnic groups (McMiller & Weisz, ).…”
Section: Disclosure and Receiving Helpmentioning
confidence: 99%
See 1 more Smart Citation
“…Mental health problems, including depression, anxiety, and substance abuse, increase suicidal risk in the general population of youth and also for Latino adolescents (Duarte‐Velez & Bernal, ; Gould et al., ). Social‐ecological factors are also strongly related to increased suicidal risk, including factors such as family conflict (O'Donnell, O'Donnell, Wardlaw, & Stueve, ; Zayas, ), lack of trusted adults to turn to during times of distress (Whitlock, ), and having a peer who engages in suicidal behavior (De Luca & Wyman, ). Increasing adolescents' acceptance to obtain more formal support (i.e., mental health services) has emerged as a salient topic in suicide prevention efforts (Husky et al., ) as those most at risk for suicidal behaviors tend to seek help only from their peers (Raviv, Raviv, Vago‐Gefen, & Fink, ) and are less likely to get support from trusted adults (Pagura, Fotti, Katz, & Sareen, ).…”
mentioning
confidence: 99%